Albert Fink papers - Fink, Albert, 1827-1897.
Drafts of unpublished papers on iron railroad bridge construction and on the Baltimore and Ohio Railroad (in German; circa 1850); reprints and pamphlets reflecting Fink's work in the post-bellum period as a railroad engineer and manager with the Louisville & Nashville Railroad, the Southern Railway & Steamship Association, and the Trunk Line Association (N.Y.); drawings and tracings of bridge and railroad construction projects supervised or designed by Fink; and sketches of his design (circa 1859) for the Jefferson County Courthouse, Louisville, Ky.
Railway construction engineer, railroad executive, and architect.
Collection material in English, with German.
Keywords: Baltimore and Ohio Railroad Company; Louisville and Nashville Railroad Company; Southern Railway and Steamship Association; Trunk Line Association (N.Y.); Architecture; Bridges -- Design and construction; Courthouses -- Kentucky; Railroad bridges; Railroad engineering; Railroads -- Design and construction; Railroads -- Management; Jefferson County Courthouse (Louisville, Ky.); Architects; Executives; Railroad engineers